Developing a foreign language policy in Greek higher education (HE): striving between Scylla and Charybdis. - TSELIGKA, THEODORA (International Journal of Language, Translation and Intercultural Communication, 2016)
The present study analyses foreign language (FL) policy in Greek higher education (HE) taking into consideration the multiple interrelated factors that development and implementation of a successful FL policy hinges on. A brief overview is presented of European initiatives that have contributed significantly to the promotion of language learning, multilingualism and the harmonization of university language policies. This was considered necessary so as to lay the context for the presentation of the practices documented in the Greek HE arena, with specific examples provided from Greek institutions. To address the aims of this research project, the state legislation relevant to FL issues in HE is examined and discussed, as it unavoidably influences and mirrors observed trends and priorities in language education. Finally, extensive data is analysed from five Greek HE institutions and their FL instructors, with regard to language practices implemented, programmes of study, instructors’ professional status, etc. The results of this analysis show that great effort and extensive co-operation among all stakeholders is still required in devising a holistic FL policy in Greek HE, to which end this paper also offers some useful recommendations.